The Remains of a Press in the Courtyard of the Roman Villa in Madona Bay on Briuni Island ("Kastrum") (Archaeologia Adriatica, 2008)
The excavation of the archaeological site in Madona Bay (Dobrika Bay, Porto Buon) on the western coast of the island of Veliki Brijun (1976–1984) uncovered a complex layering of a settlement that in various forms extended from the middle of the 1st century BC to the medieval period. Most attention to date has been attracted by the second phase, which is usually dated to the beginning of the 1st century AD: a classic Roman villa rustica, typical in terms of its shape with a central courtyard (or atrium) and rooms along three sides. The transformation of the villa into a late Roman settlement began in the 4th century with rebuilding and new construction in the courtyard of the classical villa. This was when the presses were made that are the main subject of this article. Only after this, in the 5th and 6th centuries, were the other parts of the settlement created, along with enclosing walls.Between the 4th and 6th centuries in the area of the courtyard of the earlier Roman classical villa a series of rooms was built that completely blocked off the formerly open courtyard. In the sections closest to the sea are three presses that all have the same technical characteristics, but are each different in terms of details. These were presses for oil, with a horizontal beam and winch that was built into a hollow in the floor. The length of the beams (9-10 m) places them in the category of large presses. They are quite identical technologically and contemporaneous chronologically but they were not created according to a unified plan, in a coordinated manner, rather each was constructed individually. We cannot know if the presses in the classical Roman villa were then still in use; probably not, as for some unknown reason they had proven impractical. Our three presses are entirely new structures, perhaps built after a brief interruption of life at the site, probably because a renewed need for such presses. Agricultural production again began to increase, and olives again became important for the local economy. The use of these presses was perhaps most intensive at the transition from the 5th to the 6th centuries, when the praetorian prefect at the court of the Ostrogothic King Theodoric, the senator Cassiodorus, praised this region in his letters for its fertility and the wealth of crops.
Keywords: Istria; Briuni; Roman villa; olive oil